Compreendendo a influência dos métodos de restauração na diversidade filogenética de arbóreas na Mata Atlântica - RENATA DIAS SILVA (2022)
When starting a restoration project, some considerations of the area are required aiming more appropriate choices for its recovery. Among the alternatives, the restoration method (active or passive) is a relevant decision and should be made according to the project aims, availability of financial resources, level of resilience, and land use history of the site. The Society for Ecological Restoration International suggests the evaluation of attributes to determine the success of ecological restoration, and diversity is one of these attributes. Amongst several possibilities of diversity types, phylogenetic diversity is a clue of evolutionary history of communities. Hence, our aim was to evaluate which restoration method, active or passive, promotes a greater phylogenetic diversity of tree species in Atlantic Forest restoration areas, considering age, forest cover and soil as factors known to affect the rate of forest recovery. We evaluated tree species from 36 passive restoration areas and 13 active restoration areas present in the State of São Paulo, using phylogenetic diversity as a metric. We compared the phylogenetic diversity between the restoration methods and verified whether phylogenetic diversity was influenced by the restoration method, restoration time, and/or sand percentage by using a PCoA and generalized linear model (GLM). Our study showed that the recovery of the phylogenetic diversity of the community was similar for both restoration strategies, inserted in similar landscape matrices. Hence, restoration sites with passive and active strategies can provide similar values​​of phylogenetic recovery, also favoring the colonization of locally adapted native genotypes, able to build resilient ecosystems.